Geochemical Dispersion of Copper in Lake Bottom Sediments of Lokken Area, Norway - Mallick, Khalil A.; Hasnain, S.M.; Khan, E.A.; Farooqui, M.A. (Journal of Himalayan Earth Sciences, 1991)
Bottom sediments and water were sampled from the desired sites of lakes to study the dispersion of copper in contaminated and virgin lakes of Lokken area, Central Norway. This study was an effort to use the information as a tool for the geochemical exploration of ore deposits in glaciated terrain with higher density of lakes and poor rock exposures. For the above objective frozen lake sediments and water were collected by designing and fabricating new samplers in the work shop of Geological Survey of Norway at Trondheim. The results of the present work are encouraging both in the field of instrumentation and the study of dispersion of copper to be used as a tool in the geochemical exploration of ore deposits.